Power control optimization for large-scale multi-antenna systems - Zhou, Zhenyu; Yu, Haijun; Mumtaz, Shahid; Al-Rubaye, Saba; Tsourdos, Antonios; Qingyang Hu, Rose (IEEE, 2020)
Large-scale multi-antenna systems can effectively improve data transmission reliability and throughput for smart grid. However, the massive number of antennas and radio frequency (RF) chains also result in high complexity and energy cost. In this paper, we develop a new performance benchmark named energy economic efficiency for measuring the time-average throughput per energy cost. Then, we investigate how to maximize long-term energy economic efficiency via the joint optimization of communication and energy resource allocation. The formulated joint optimization problem is NP-hard because it not only involves long-term nonlinear optimization objective and constraints, but also involves both integer and continuous optimization variables. Next, we propose an online joint antenna selection and power control algorithm by combining nonlinear fractional programming, Lyapunov optimization, and bisection method. The proposed algorithm can achieve bounded performance deviation from the optimum performance without requiring the prior knowledge of future channel state information (CSI), energy arrival, and electricity price. Finally, a comprehensive theoretical analysis is provided, and the proposed algorithm is verified through simulations under various system configurations.
Keywords: Large-scale multi-antenna systems; Lyapunov optimization; smart grid; energy economic efficiency; bisection method; nonlinear fractional programming